A founder’s strategy and entrepreneurial leadership are critical elements in growing and developing a mid-sized venture - Van Vuuren, Jurie Jansen (University of Pretoria, 2013)
Thesis (PhD (Entrepreneurship))--University of Pretoria, 2006.